A case of adrenal lymphangioma resected laparoscopically with minimal invasiveness - Hiroshi Yaegashi; Takahiro Nohara; Kazuyoshi Shigehara; Kouji Izumi; Yoshifumi Kadono; Atsushi Mizokami (Urology Case Reports, 2020)
A 33-year-old female presented to us with a left adrenal cystic tumor with a maximum diameter of 70 mm. Because malignant tumor and pheochromocytoma could not be excluded, she underwent left laparoscopic transperitoneal adrenalectomy. The cystic tumor was stored to an endoscopically inactive treatment device and was subsequently punctured within the device; thus, tumor removal could be performed with minimum incision. Pathological findings showed highly suggestive of a cystic lymphangioma. The punctate was found to have an extremely high catecholamine titer. To avoid unnecessarily exposing the tumor contents, the treatment approach described in this report is reasonable and worth reporting.